Synthesis and Characterization of Hydrogels based on Graft Copolymerization of Acrylamide on Chitin resulted from Enzymatic Isolation of Shrimp Waste - Lestari, Tia; Sjaifullah, Achmad; Santoso, Agung Budi (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2016)
Shrimp waste containing chitin 15-20%. Chitin can be isolated enzymatically by using proteaseenzymes derived from the waste itself. Waste of shrimp marinated in 1M H2SO4 for 10 days at pH1-2 and do control the pH and concentration of N-total every 24 hours. So that, this process canreduce the use of chemicals and environmental pollution. Enzymatic chitin obtained ash content1.789% and 5.322% of N-total. Results of IR showed characteristic functional groups of chitin areOH 3390.5 cm-1, NH (secondary amide) 3348.71 cm-1, C = O 1648.20 cm-1, C-N at 1313.96 cm-1,C-O 1115, 28 cm-1. Chitin is dissolved in 8% NaOH / Urea 4% for 36 hours (-20oC). Hydrogelsmade with a ratio (1: 6); (1: 8); (1:16); (1:24) w / w. The results showed the increasing amount ofacrylamide monomer, the greater the value% graft and absorption of water. Enzymatic chitinhydrogel showed the maximum value % graft is 2492.073%; and water absorption 1.794 g / g. IRhydrogel results indicate primary amide N-H stretching of acrylamide at 3349.77 and 3202.88 cm-1, C = O 1662.03 cm-1Keywords: hydrogel, chitin, acrylamide, graft copolymerization